The Budget management and effective supply of strategic goods in the Social Health Insurance - Correa , Luis (2021)
The objective of this study was to demonstrate the relationship between budget management and the effective supply of strategic goods in the Social Health Security. The sample consisted of 134 workers from the Central Management of Planning and Budget and Supply of Strategic Assets of the Social Health Security, who were evaluated by means of a questionnaire of their own authorship. A mixed approach was used, with a concurrent nested design of the dominant model type with qualitative emphasis and quantitative insertion, with a descriptive, explanatory and correlational scope. The results showed that, within the dimensions of budget management, 92.5% of those surveyed perceive a good level in budget control; Likewise, 98.5% show a good level in the storage and supply of strategic goods as a dimension effectiveness of the supply of strategic goods. In addition, there is a direct and significant correlation of a moderate level (r = 0.411; p <0.05) between budget management and the effectiveness of the supply of strategic goods; Finally, it was concluded the budget management turned out to be significantly related to the effective supply of strategic goods.